(untitled) (Educational Knowledge, 2022)
The processes involved in the organization and management of educational centers are implemented through management models with an open, flexible, and participatory approach, responding to the needs of the educational situation. This study aims to determine the management styles of principals in educational centers in the city of Luque, Republic of Paraguay, during the year 2020. To understand the profile of these educational managers, the study seeks to identify their main functions and specify the conditioning factors that influence their management. A descriptive, quantitative, non-experimental, cross-sectional, and time-bound research approach was used. Initially, a literature review on the topic was conducted. Subsequently, a survey was developed and administered to 63 principals to obtain the results, which then allowed for analysis and interpretation. The main finding is that the majority of principals are winners of competitive selection processes, particularly women entering the profession. In this way, the hypothesis initially proposed has been validated, since the Directors of educational centers promote participatory management and leadership styles focused on concrete actions to improve educational management.